Comparison of Breast Cancer 3-years Survival Rate Based on the Pathological Stages - Nur Imroatul Mursyidah; Ami Ashariati; Etty Hary Kusumastuti (Faculty of Medicine Universitas Airlangga, 2019)
Introduction: The aims of this study was to determine the differences of breast cancer survival rate based on Pathological stages.Methods: This study was conducted with a retrospective case control design using secondary data from Dr. Soetomo General Hospital's medical records. The technique used to take the samples was purposive sampling. The sample was 45 breast cancer patients in Dr. Soetomo General Hospital In January 2015, that able to be contacted again and had a medical record in the oncology center in Dr. Soetomo General Hospital Surabaya. The variables studied is breast cancer survival based on the pathological stages.Results: Breast cancer patients at the stage of IIA have 100% 3-year survival rate, stage IIB by 83.3%, stage IIIA by 71.4%, stage IIIB by 53.8%, IIIC by 50%, and stage IV by 30%. With a comparison of the log-rank significance p = 0.104.Conclusion: The survival rate of breast cancer patients is lower in line with the increasing pathological stage of breast cancer.